Meeting the challenges of food-energy-water systems in typical mega-urban regions from final demands and supply chains: A case study of the Bohai mega-urban region, China. (20th October 2021) - Deng, Caiyun; Wang, Hongrui; Hong, Siyang; Zhao, Weijing; Wang, Cheng
Abstract: The safety of food-energy-water (FEW) systems in mega-urban regions (MURs) is an urgent issue for achieving regional sustainable development. However, with the rapid growth of the population, the economy and urbanization and uncertainty inherent in climate change and international politics, FEW systems in MURs face tremendous challenges not only because of increasing demands and inadequate resources but also because of the dependence on imports from other regions. Therefore, it is essential to identify the critical connections and change features in FEW systems from economic actions to better meet these challenges. Taking the Bohai MUR as a case study, this study explores FEW changes embodied in trade, final demands and supply chains during 2002–2012 and identifies important nodes and critical supply chains by combining a three-scale input-output (IO) model with structural path analysis (SPA). The results show that FEW flows embodied in trade were significantly increased during the 10 years. The Bohai MUR turned from a net importer to a net exporter in embodied food and energy from 2002 to 2012. In final demands, the ratios of consumption and investment in embodied FEW obviously decreased, but exports increased significantly. Exports were always the largest consumer of embodied FEW, and urban households also consumed them. The top 20 critical supply chains from the final demands to the upstream production sectors for food, energy and water systems in 2002 and 2012 are listed. One and three common routes in the top 5 critical supply chains strongly impact embodied FEW. The common critical routes of each subsystem in time are also identified. Embodied FEW change factors and coping strategies are explored as well. This study will help stakeholders make responsible production and consumption decisions to improve the resilience of FEW systems and achieve sustainable development goals (SDGs) at the mega-urban scale. Highlights: MSIO analysis and SPA are combined to explore embodied FEW in an MUR for the first time. Embodied food and energy significantly change from a net importer to a net exporter. AFT, MAN, UC and exports are the most important key nodes along the supply chains. Common critical supply chains of embodied FEW and their changes are identified. Coping strategies to meet challenges in FEW systems in the Bohai MUR are suggested.